Impact of Urbanization on Vegetation Cover in Gombe Metropolis and Environs (Global Journal of Human-Social Science, 2019)
Demographic characteristics and economic development are the major determinants of urban shape and pattern of urbanization in Gombe which gave rise to rapid population growth. These determinants resulted to unplanned urban growth, unprecedented urbanization and land use change as a result contributing in the rapid reduction of vegetation cover and loss of arable land in the surrounding urban environment. The aim of this paper is on the impact of urbanization on vegetation cover. Both primary and secondary data was employed in this work. Socioeconomic data and information on the status of tree species were gathered through questionnaire survey that involved 195 respondents using purposive sampling techniques in the study area. While the land use land cover analysis was carried out using ArcGis 10.5 and Edras Imagine 9.0. The finding was made to capture as accurate as possible six land use land cover classes as they changed through time.
Keywords: environment; urbanization; vegetation; population; expansion